Intervensi Health Coaching dalam Meningkatkan Self-Care Management Pasien Heart Failure - Asriyani Hamid; Elly L Sjattar; Kusrini S Kadar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the literature that explores health coaching interventions in improving Heart Failure (HF) self-care management, focusing on the total duration and type of health coaching media. The research method uses literature reviews by tracing publications between 2017-2020, the Cochrane database, PubMed, ScienceDirect, ProQuest, and Garuda. The results identified five health coaching studies according to inclusion criteria and resulted in significant improvements in HF self-care management, including symptom reporting, increased physical activity, low-salt diet, fluid and drug intake, self-efficacy, adherence to measuring body weight and blood pressure, and changes. Lifestyle, even though there are differences in the health training methods used. In conclusion, the duration and different media from each study did not significantly influence improving HF self-care management. Keywords: Heart Failure, Self-Care Management, Health Development